The Role of Quality of Work Life and Job Satisfaction in Mediating the Influence of Organizational Justice on Employee Commitment - Mulyati, Ni Kadek Dwi; Landra, Nengah; Aristana, I Nengah (Journal of Social Work and Science Education, 2024)
This study aims to determine the role of quality of work life and job satisfaction in mediating the influence of organizational justice on employee commitment at the UPTD Puskesmas Dawan II, Klungkung Regency. The population used in this study was 69 employees, the sample in this study was 69 employees. The data analysis technique used was Patrial Least Square (PLS) using Smart PLS 4.0.9 software. The results of this study indicate that organizational justice has a positive and significant direct effect on employee commitment. Organizational justice has a positive and significant direct effect on the quality of work life. Organizational justice has a positive and significant direct effect on job satisfaction. The quality of work life has a positive and significant direct effect on employee commitment. Job satisfaction has a positive and significant direct effect on employee commitment. The quality of work life is able to partially mediate the effect of organizational justice on employee commitment. Job satisfaction is able to partially mediate the effect of organizational justice on employee commitment. It is recommended that employees are able to increase their self-confidence, and the company must be able to regulate employee working hours to suit the company's expectations, job satisfaction as one of the considerations in efforts to increase employee commitment.